2013
DOI: 10.1007/s40069-013-0042-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Heavy Oil Fly Ash as a Color Ingredient in Cement Mortar

Abstract: Heavy oil fly ash (HOFA) is a byproduct generated by the burning of heavy fuel oil. Chemical analysis showed that HOFA is mainly composed of unburned carbon with a significant amount of heavy metals. Due to toxicity, management of this waste poses a challenge to the industry personal. The present study investigates the possible use of HOFA as a black pigment or admixture in cement mortar aiming to produce ornamental brick. In order to investigate the change of cement mortar strength when HOFA is added, the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…concluded from the XRD analysis that HFOA consists of amorphous carbon and crystallites of metallic oxides, such as quartz, faujasite, aluminosilicate (mullite), zeolite, and cancrinite [30] . Similarly, other groups have reported the amorphous nature of carbon [26,29,31,32,33,34] . In contrast, Al Ghouti et al., using XRD analysis, reported that carbon in HFOA generated in a Jordanian thermal power plant was crystalline in nature [17] .…”
Section: Characteristics Of Hfoamentioning
confidence: 99%
See 3 more Smart Citations
“…concluded from the XRD analysis that HFOA consists of amorphous carbon and crystallites of metallic oxides, such as quartz, faujasite, aluminosilicate (mullite), zeolite, and cancrinite [30] . Similarly, other groups have reported the amorphous nature of carbon [26,29,31,32,33,34] . In contrast, Al Ghouti et al., using XRD analysis, reported that carbon in HFOA generated in a Jordanian thermal power plant was crystalline in nature [17] .…”
Section: Characteristics Of Hfoamentioning
confidence: 99%
“…[30] Similarly, other groups have reported the amorphous nature of carbon. [26,29,31,32,33,34] In contrast, Al Ghouti et al, using XRD analysis, reported that carbon in HFOA generated in a Jordanian thermal power plant was crystalline in nature. [17] Likewise, it was reported to be crystalline in other studies.…”
Section: Structural Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Coal fly ash can be categorized into two distinct classes, i.e., F and C. Class F fly ash is produced as a result of burning anthracite or sometimes bituminous coal. On the other hand, class C fly ash is produced by burning sub-bituminous coal or lignite [1]. This classification is based on the sum of the major oxides present in the fly ash, such as silicon dioxide (SiO 2 ), ferric oxide (Fe 2 O 3 ) and aluminum oxide (Al 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%